Knowledge management best practices in national sport organisations. (12th February 2007) - O'Reilly, Norman J.; Knight, Peter
Knowledge Management (KM), or the ability to effectively use, share and create knowledge to facilitate individual, team, and organisational learning is important in all organisations. KM encompasses a broad range of tools, technologies, and managerial practices intended to produce bottom line benefits by making better use of an organisation's intellectual capital and it has become an increasingly important consideration given the challenges of managing vast amounts of information. National Sport Organizations (NSO) are not-for-profit organisations that are responsible for the development of their particular sport in their own country. Workplace tools and structures that efficiently facilitate the sharing and creation of knowledge are important to the survival and growth of these organisations. The purpose of this research is to build an initial research framework that will guide research toward a better understanding of KM practices which facilitate learning and thus improve performance of not-for-profit, volunteer managed organisations.